(untitled) (Journal of the College of Education for Women, 2019)
This study comes to be as an attempt by the researcher toparticipate in gathering part of the heritage of the Arab nation which isdispersed between the historical and literary sources and references.The study also aims to accumulate and achieve poetry to be moreuseful and effective in the productions of the researchers and scholarsof Arabic literature and history.The research is an extension of eight handwritings studied bythe researcher for the same poet. These handwritings are found in theform of five eulogistic stanzas about the great prophet (may peace beupon him). Therefore, the researcher decides to reveal what otherresearchers have transcended but from the side of concern and beliefin the importance of clarification or presentation.